(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2020)
This work describes the chemical characterization of extracts of Jatropha gossypiifolia (from Amazonia region) concerning the presence of phenolic and triterpenic compounds using Ultra High Perfomance Liquid chromatography coupled to Mass Spectrometry in Tandem (UHPLC-MS/MS) methods. The studied compounds belong to the most frequently found classes in medicinal plants (triterpenes, flavonoids, flavones, hydroxycinnamic acids, coumarins, catechins and stilbenes), which have been analyzed as chemical and bioactive markers in hydroethanolic and aqueous extracts. Several polyphenolic compounds identified herein are unprecedented in the scientific literature for this species. The chemical markers identified and quantified in the studied extracts of J. gossypiifolia were gallic acid, chlorogenic acid, catechin, caffeic acid, vanillic acid, p-coumaric acid, ferullic acid, rutin, quercitrin, 3-acetylcoumarin, trans-cinnamic acid, quercetin, luteolin, apigenin, kaempferol, chrysin. α-amyrin, β-amyrin and lupeol. As the majority compounds, (+)-catechin, p-coumaric acid, ferulic acid, luteolin, α-amyrin and β-amyrin were found to be present at mg kg−1 levels. J. gossypiifolia extracts presented a high in vitro activity against different reactive oxygen species (hydroxyl, peroxyl, and superoxide anion radicals). Several polyphenolic compound data presented herein are unprecedented in the scientific literature for this plant species. As a result, this plant can be a new source of bioactive molecules for therapeutic purposes.